2018
DOI: 10.2478/pjst-2018-0014
|View full text |Cite
|
Sign up to set email alerts
|

Offensive and Defensive Play in Handball in a 2-Year World Championship Cycle: Characteristics and Tendencies

Abstract: Introduction. The analysis of players’ performance with respect to technical-tactical actions is becoming a key factor influencing the focus of training programmes and the contents of training units. It also provides important information which can be used to improve players’ efficiency during the game. The aim of the current study was to analyse the efficiency of technicaltactical offensive actions in positional attack as well as defensive actions performed by handball players participating in two consecutive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…However, under further investigation over the tactical situation, it's very important to highlight significant decrease of the quantity of distance shots, which are likely to be linked with the character of handball and the handball player silhouette [12]. Gryko et al [6] informed about decreasing number of 9 meter shots which has leveled at average of 17.3 shot per game in World Championships in 2015 and was significantly lower than in 2013 (-9.9%, p<0.05). In EHF EURO 2022, mean number of distance shots per game was only 11.9 what proves changing character of the game over last few years.…”
Section: Discussionmentioning
confidence: 99%
“…However, under further investigation over the tactical situation, it's very important to highlight significant decrease of the quantity of distance shots, which are likely to be linked with the character of handball and the handball player silhouette [12]. Gryko et al [6] informed about decreasing number of 9 meter shots which has leveled at average of 17.3 shot per game in World Championships in 2015 and was significantly lower than in 2013 (-9.9%, p<0.05). In EHF EURO 2022, mean number of distance shots per game was only 11.9 what proves changing character of the game over last few years.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the numerical relationship between teams, we concluded that the chance of an offensive sequence ending successfully is 1.38 times higher when the observed team has a numerical advantage, whereas having fewer players on the field leads to a 36% decrease in the success rate of offensive sequences. In this sense, there seems to be a clear benefit to the teams that take advantage of situations when they have numerical superiority due to a 2-min sanction imposed on a player of the opposing team (Fasold and Redlich, 2018;Gryko et al, 2018).…”
Section: Total Of Passesmentioning
confidence: 99%
“…The following studies present indication related to other comparative analyses among several indicators in a handball match analysis. (Fasold & Redlich, 2018;Gryko, Bodasiński, Bodasińska, & Zieliński, 2018;Hatzimanouil, Giatsis, Kepesidou, Kanioglou, & Loizos, 2017;Meletakos & Bayios, 2010;Meletakos, Vagenas, & Bayios, 2011;Prieto, Gómez, & Sampaio, 2015a;Prudente, Sousa, Sequeira, Lopez-Lopez, & Hernandez-Mendo, 2017) (Table 5). This review was to determine the key indicators of discrimination in a comparative analysis between winners and losers.…”
Section: Tests Of Wilcoxon Test Of Mann-whitney U the Kruskal-wallis Testmentioning
confidence: 99%
“…In identifying the offensive and defensive situations during a two-year cycle, Gryko et al (2018) detects a change in the concept of playing in the positional attack in the 2015 championship in comparison to the 2013 championship; there were a significantly greater number of actions that led to a pitch in the region of 6 metres next to an opponent's goal area, as well as a higher level of actions and a more aggressive game by the defensive players; the European teams won more games than the teams of other continents, demonstrating a superiority in the effectiveness of the technical-tactical actions of the match.…”
Section: Other Comparative Studiesmentioning
confidence: 99%